Myocardial T1 mapping: modalities and clinical applications - Jellis, Christine L.; Kwon, Deborah H. (Cardiovascular Diagnosis and Therapy, 2013)
Myocardial fibrosis appears to be linked to myocardial dysfunction in a multitude of nonischemic cardiomyopathies. Accurate non-invasive quantitation of this extra-cellular matrix has the potential for widespread clinical benefit in both diagnosis and guiding therapeutic intervention. T1 mapping is a cardiac magnetic resonance (CMR) imaging technique, which shows early clinical promise particularly in the setting of diffuse fibrosis. This review will outline the evolution of T1 mapping and the various techniques available with their inherent advantages and limitations. Histological validation of this technique remains somewhat limited, however clinical application in a range of pathologies suggests strong potential for future development.